2022
DOI: 10.1002/rse2.296
|View full text |Cite
|
Sign up to set email alerts
|

Widespread drought‐induced leaf shedding and legacy effects on productivity in European deciduous forests

Abstract: Heatwaves and droughts are becoming more common and severe in Europe, causing changes in tree phenology, disrupting the sequestration of carbon and causing tree mortality on a continental scale. The responses of leaf shedding to heatwaves and droughts remain uncertain, although temperate deciduous forests may shed their leaves if exposed to extreme heat and water stress. Little information, however, is available about the extent and recurrence of early leaf shedding induced by drought, likely because it occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Both Descals et al [116] and Brun et al [38] demonstrated the impact of the severe 2018 drought in Central Europe on temperate forests and the resulting early leaf shedding. While Descals et al [116] confirmed that early leaf shedding occurred during the entire study period (2017-2021), increased in extent…”
Section: Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Descals et al [116] and Brun et al [38] demonstrated the impact of the severe 2018 drought in Central Europe on temperate forests and the resulting early leaf shedding. While Descals et al [116] confirmed that early leaf shedding occurred during the entire study period (2017-2021), increased in extent…”
Section: Droughtmentioning
confidence: 99%
“…Three studies investigated the extent to which drought events induced early wilting. Using multispectral timeseries from MODIS and Sentinel-2, changes in the NDVI or EVI signal could be attributed to early leaf shedding [38,116,117]. Both Descals et al [116] and Brun et al [38] demonstrated the impact of the severe 2018 drought in Central Europe on temperate forests and the resulting early leaf shedding.…”
Section: Droughtmentioning
confidence: 99%
“…In addition, satellite TS analysis shows an increased trend in the frequency and intensity of droughts, and illustrative studies have been conducted for northern Europe (e.g. Reinermann et al, 2019;Senf et al, 2020;Descals et al, 2023). Climate change is also increasing the frequency of biotic disturbances like insect outbreaks (Senf et al, 2017;Olsson et al, 2017).…”
Section: Applications In Forestrymentioning
confidence: 99%
“…These climate projections could be even more detrimental if models would not neglect, as they currently do, feedback in the carbon cycle and potential tipping points that could generate higher GHG concentrations [ 4 ]. Examples include the apparent slowing of dampening feedbacks such as the natural carbon-sink capacity [ 5 , 6 ], the loss of carbon due to increasing frequencies and intensities of fire at northern latitudes [ 7 ], droughts and fires in the Amazon [ 8 ] or the thawing of Arctic permafrost that releases methane and CO 2 [ 9 ]. This feedback is also likely not proportional to warming, as is sometimes assumed.…”
mentioning
confidence: 99%
“…This feedback is also likely not proportional to warming, as is sometimes assumed. Instead, abrupt and/or irreversible changes may be triggered at a temperature threshold [ 7 ]. Particularly worrying is a ‘tipping cascade’ in which multiple tipping elements interact in such a way that tipping one threshold increases the likelihood of tipping another [ 4 , 10 ].…”
mentioning
confidence: 99%